2020
DOI: 10.3389/fgene.2019.01290
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress-Related Gene Polymorphisms Are Associated With Hepatitis B Virus-Induced Liver Disease in the Northern Chinese Han Population

Abstract: Oxidative stress is closely related to the occurrence and development of various diseases such as cancer, diabetes, and cardiovascular and infectious diseases. We identified six critical genetic variants related to oxidative stress, and evaluated their main effects and their interaction effects on hepatitis B virus (HBV)-induced liver diseases. We enrolled 3,128 Han Chinese subjects into five groups: healthy controls, chronic hepatitis B (CHB), liver cirrhosis (LC), hepatocellular carcinoma (HCC), and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…SLC1A5 may serve as a potential target for enhancing anti-tumour immunity in the tumour microenvironment ( 27 ). According to the literature, GCLM gene polymorphisms are associated with hepatitis B virus-induced liver disease ( 28 ). There is limited research on BOD1, GDI2, GTF3C6 and ERI3’ impact on hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…SLC1A5 may serve as a potential target for enhancing anti-tumour immunity in the tumour microenvironment ( 27 ). According to the literature, GCLM gene polymorphisms are associated with hepatitis B virus-induced liver disease ( 28 ). There is limited research on BOD1, GDI2, GTF3C6 and ERI3’ impact on hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…As con rmed in RT-PCR results GADD45B was up regulated during infection and SOD2 is slightly up regulate until 6hpi. The DEG CYBA encoded protein is a crucial subunit of NADPH oxidase involve in oxidative stress, and researchers have studied its role in HCV and HBV disease mechanism 28,29 . In both RNA-seq and RT-PCR result, CYBA was down regulated during virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the T allele was associated with an increase of chromosomal deletions indicative of defects in BER pathway and with a lower survival time of patients with different types of cancer [44][45][46]. Moreover, in vitro and in vivo studies demonstrated that HBV can induce reactive oxygen species (ROS) production that causes oxidative stress resulting in hepatocyte injury [47][48][49]. As XRCC1 is one of the main players in the repair of ROS-induced lesions [50], it brings us to the conclusion that affecting protein function rs25487 may have an impact on HBV-induced liver fibrosis development.…”
Section: Discussionmentioning
confidence: 99%